Unusual Presentation of Chikungunya Virus Infection With Concomintant Erysipelas in a Returning Traveler From the Caribbean: A Case Report. (20th November 2014) - Schechter, Marcos C.; Workowski, Kimberly A.; Fairley, Jessica K.
Abstract: Chikungunya fever is a mosquito-borne febrile illness caused by Chikungunya virus (CHIKV), an alphavirus from the Togaviridae family. It is transmitted by primarily Aedes aegytpi and Aedes albopictus mosquitos [1 ]. Once of little importance in the Americas, local transmission was identified in the Caribbean in late 2013. More than 1000 travelers returning to the continental United States have been diagnosed with CHIKV. More importantly, there have been 9 documented cases of autochthonous disease in Florida as of September 16, 2014 [2 ].